Identify a sequence of rigid transformations that would map ABCD -> A" B" C" D". Give your answer in the form of a composition transformation mapping.

a. (x,y) -> (-x -4, y)
b. (x,y) -> (-x, y - 4)
c. (x,y) -> (x, y + 4)
d. (x,y) -> (x, - y - 4)

1 answer

To identify a sequence of rigid transformations that would map quadrilateral ABCD to A"B"C"D", we need to analyze what each transformation does.

  1. Option a: (x,y) -> (-x - 4, y)

    • This transformation reflects the point over the y-axis and then shifts it left by 4 units.
  2. Option b: (x,y) -> (-x, y - 4)

    • This transformation reflects the point over the y-axis and then shifts it down by 4 units.
  3. Option c: (x,y) -> (x, y + 4)

    • This transformation shifts the point up by 4 units.
  4. Option d: (x,y) -> (x, -y - 4)

    • This transformation reflects the point over the x-axis and then shifts it down by 4 units.

Now, let's construct a composition of transformations that will map ABCD to A"B"C"D".

Based on the nature of transformations, we can start with a reflection and translations.

To outline an example sequence:

  1. Apply transformation d: (x,y) -> (x, -y - 4)
    This would reflect the points over the x-axis and shift them down.

  2. Follow it with transformation c: (x,y) -> (x, y + 4)
    This shifts the resulting points up by 4.

Thus, the resulting composition of transformations will be:

\[ (x,y) \xrightarrow{d} (x, -y - 4) \xrightarrow{c} (x, -(-y - 4) + 4) = (x, y) \]

However, to map ABCD specifically to A"B"C"D" may require a precise arrangement or specific parameters around the specific shape and placement of points.

To codify the transformations in our required mapping:

  1. First use option d.
  2. Use option c afterwards.

So you would write the final composition transformation as: d followed by c:

\[ (x,y) \xrightarrow{d} (x, -y - 4) \xrightarrow{c} (x, -y - 4 + 4) = (x, -y) \]

This means: Final composition: Use the transformations in the sequence as \[ d \circ c \].

In a clean answer format, you'd express it this way:

The sequence of transformations is: \( d \) followed by \( c \) (i.e., \( d \circ c \)).